Question-Answer in ‘Ayat-Ayat Cinta’ (A Study of Speech Act in Novel) - Batmang Batmang (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
This study aims to obtain information related to the forms and the uses of linkages adjacency pair of 'question-answer' used in Ayat-Ayat Cinta, as well as understand the function of the adjacent pair in establishing the integrity of the novel discourse. This study is a qualitative study which is operationally using the principles of speech act study. The speech act referred in this study is a dialogue in the novel which becomes the data source of this research. Data was collected by the following procedure: (1) to identify the overall dialogue in the novel; Ayat-Ayat Cinta; (2) to determine the adjacent pair in the form of